Multiple Disciplines Product Design Knowledge Representation Strategy Based on Ontology and Semantic Network - Guohai Zhang; Yusheng Li (Institute of Advanced Engineering and Science, 2013)
The complicated products design is a process of conflict resolution and integration decision for collaborative optimization involved in multiple disciplines including mechanical engineering, electronical engineering and control engineering, etc. It’s also a multi-disciplinary field of complex knowledge fusion process. The architecture of the product design knowledge is given by the description of the forms of knowledge in complex product design. The representation mechanism for multidisciplinary knowledge based on ontology and formal definition of the design knowledge ontology are put forward by using the theories and methods of ontology and semantic network. Finally, the multiple disciplines design knowledge expression strategy is proposed based on the above analysis and conclusions. This paper provides a new method and means for complicated product design knowledge representation involving the integration of multidisciplinary knowledge. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.3467